Virulence variation among epidemic and non-epidemic strains of Saint Louis encephalitis virus circulating in Argentina - Rivarola, María Elisa (2014)
Saint Louis encephalitis virus caused an outbreak of febrile illness and encephalitis cases in Córdoba, Argentina, in 2005. During this outbreak, the strain CbaAr-4005 was isolated from Culex quinquefasciatus mosquitoes. We hypothesised that this epidemic variant would be more virulent in a mouse model than two other non-epidemic strains (78V-6507 and CorAn-9275) isolated under different epidemiological conditions. To test this hypothesis, we performed a biological characterisation in a murine model, including mortality, morbidity and infection percentages and lethal infection indices using the three strains. Mice were separated into age groups (7, 10 and 21-day-old mice) and analysed after infection. The strain CbaAr-4005 was the most infective and lethal of the three variants, whereas the other two strains exhibited a decreasing mortality percentage with increasing animal age. The strain CbaAr- 4005 produced the highest morbidity percentages and no significant differences among age groups were observed. The epidemic strain caused signs of illness in all inoculated animals and showed narrower ranges from the onset of symptoms than the other strains. CbaAr-4005 was the most virulent for Swiss albino mice. Our results highlight the importance of performing biological characterisations of arbovirus strains likely to be responsible for emerging or reemerging human diseases.